PEMBERDAYAAN DAN PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN BERKELANJUTAN - Juslaeni, Sri; Wahid, Nur; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the Empowerment of Women in Lamanda Village, Bontotiro District, Bulukumba Regency. This study uses a qualitative method with a descriptive type. Data collection techniques include observation, interviews and documentation. The results of the research can be seen from the Access Aspect, by creating a forum or organization for Indonesian women and having outlined the forms of women's roles in development, the government thus hopes that the role of Indonesian women in development can increase, from the aspect of participation, community involvement at every stage development starts from planning, implementation, utilization and maintenance, will foster a sense of trust in the government so that people are motivated to support development programs carried out by the government. In terms of control, that women have the same opportunity to exercise control over the utilization of existing resources.